2015
DOI: 10.18052/www.scipress.com/ilns.48.23
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Seed Germination and Embryo Culture in <i>Nothapodytes foetida</i> (Wight) Sleumer

Abstract: ABSTRACT. In vitro seed germination and embryo culture have been achieved in Nothapodytes foetida, this plant is known for its rich source of anticancer drug i. e., Camptothecin. In present study both normal and decoated seeds were subjected to different treatments viz., H2O, GA 3 , H2O2, H2SO4, chlorine water and mechanical scarification, further these were germinated on water agar medium (WA), filter paper bridge (FB), half strength MS (HMS) and full strength MS (FMS) medium. The highest percentage (69%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…In the present study, the germination percentage of N. oleander zygotic embryos was found much higher than the wild mature seeds in the culture medium, which might be due to the presence of various inhibitors in the seed coat (Kaveri & Rao, 2015). However, some other direct (Karrunakaran & Shri, 2010;Hatzilazarou et al, 2019) and indirect in vitro micropropagation techniques are reported from this plant (DH Paper, 1989;Santos et al, 1994;Vila et al, 2010) yet no ZEC and CGs profiling of acclimatized and in vitro raised plants found to be reported in our knowledge.…”
Section: Discussioncontrasting
confidence: 64%
“…In the present study, the germination percentage of N. oleander zygotic embryos was found much higher than the wild mature seeds in the culture medium, which might be due to the presence of various inhibitors in the seed coat (Kaveri & Rao, 2015). However, some other direct (Karrunakaran & Shri, 2010;Hatzilazarou et al, 2019) and indirect in vitro micropropagation techniques are reported from this plant (DH Paper, 1989;Santos et al, 1994;Vila et al, 2010) yet no ZEC and CGs profiling of acclimatized and in vitro raised plants found to be reported in our knowledge.…”
Section: Discussioncontrasting
confidence: 64%